2023
DOI: 10.3164/jcbn.23-12
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamtannin A2, (−)-epicatechin tetramer, attenuates skeletal muscle wasting in disuse atrophy model mice induced by hindlimb suspension

Abstract: The impact of repeated administration of cinntamtannin A2 (A2, 25 μg/kg) on skeletal muscle disuse atrophy model mice induced by hindlimb suspension for 14 days was examined. In soleus, weight loss and a reduction in the average myofibre size with shifting to the smaller side of the peak were observed in the suspension-vehicle group, but A2 reduced these changes. Average myofibre size significantly increased in ground-A2 compared to ground-vehicle. A marked increase in the dephosphorylation of forkhead box O (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…This was characterized by multilocular lipid droplets, a marked reduction in adipocyte size and increased expression of the heat-producing protein, uncoupling protein 1 (UCP-1) [118]. Repeated administration of the flavanol cinnamtannin A2 (A2, epicatechin tetramer) for two weeks also resulted in significant activation of the Akt/mTOR pathway and a marked increase in the mean muscle cross-sectional area in the soleus muscle [119] as similar to adrenalin agonist clenbuterol [120]. It has also been observed that after a single dose of flavanol, blood catecholamine levels were significantly increased [121] and urinary catecholamine excretion was also elevated [118].…”
Section: Astringency Perception Is a Stressormentioning
confidence: 99%
“…This was characterized by multilocular lipid droplets, a marked reduction in adipocyte size and increased expression of the heat-producing protein, uncoupling protein 1 (UCP-1) [118]. Repeated administration of the flavanol cinnamtannin A2 (A2, epicatechin tetramer) for two weeks also resulted in significant activation of the Akt/mTOR pathway and a marked increase in the mean muscle cross-sectional area in the soleus muscle [119] as similar to adrenalin agonist clenbuterol [120]. It has also been observed that after a single dose of flavanol, blood catecholamine levels were significantly increased [121] and urinary catecholamine excretion was also elevated [118].…”
Section: Astringency Perception Is a Stressormentioning
confidence: 99%